Pendidikan Tasawuf dalam Nazkah Al-Malhuzat K.H. Ahmad Asrori Al-Ishaqi dan Relevansinya Terhadap Tujuan Pendidikan Nasional - Zidan Syahrul Akbar; Dwi Hizami (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
Various cases in this era which are considered due to a lack of spirituality in humans make the role of ulama in improving spirituality in this era important. The education taught by the ulama' is Sufism education in the form of tarekat and essence sharia. On the other hand, national education also has goals that are in line with Sufism education. However, this is sometimes misunderstood as a dichotomy between religion and the world. So it is important to study the ideas of religious figures and their thoughts and relate them to national education. This paper uses a descriptive analysis method with library research, because the data will be extracted from library data and uses a qualitative approach that tests the quality of ideas by answering problems based on existing theoretical foundations and by reviewing the manuscript of al-Malhuzat KH Ahmad Asrori Al-Ishaqi. The research results show that Kiai Asrori's al-Malhuzat text contains Sufism education which is a solution for improving spirituality in this era. Apart from that, Sufism education in this text is also in line with national education goals. Such as integration between sharia, tarekat and essence which has the essence of integrating the world and the afterlife, using Sufism strategies, and balancing between raja' and khauf.